Healthcare Waste Management Policy in a Lower-Middle-Income Country: A Case for the Adoption of the RADICAL Framework - Edozien, Leroy C. (Journal of Sustainable Development Law and Policy, 2025)
The COVID-19 pandemic raised the salience of Healthcare Waste Management (HCWM). Various studies have shown that the level of HCWM in lower-middle-income countries falls below international standards and global best practice, indicating that the national policy on HCWM is either nonexistent or has not been embedded in practice. The renewed salience affords an opportunity to revisit, update and embed the national policy on HCWM. In seizing this opportunity, the elemental thinking must change from a linear model to the complex adaptive model that takes account of the interrelationships and contextual factors that could impede or facilitate implementation of the policy. These complexities account for the ‘policy-implementation gap’ associated with policy failure. This paper presents a framework that could be applied in developing, implementing, and monitoring the national HCWM policy in a lower-middle-income country. The integrative framework, identified by the acronym RADICAL, comprises the following domains in an integrated grid: Raise awareness; Apply formal quality improvement methods; Design for quality and safety: Involve stakeholders; Collect and Analyse pertinent data; Learn from shared experience. The pertinence of each domain to HCWM is described.